Design of Low Power UWB CMOS Low Noise Amplifier using Active Inductor for WLAN Receiver - Manjula, S; Malleshwari, M; Suganthy, M (International Journal of Engineering and Technology, 2018)
This paper presents a low power Low Noise Amplifier (LNA) using 0.18Âµm CMOS technology for ultra wide band (UWB) applications. gm boosting common gate (CG) LNA is designed to improve the noise performance.Â For the reduction of on chip area, active inductor is employed at the input side of the designed LNA for input impedance matching. The proposed UWB LNA is designed using Advanced Design SystemÂ (ADS) at UWB frequency of 3.1-10.6 GHz. Simulation results show that the gain of 10.74+ 0.01 dB, noise figure is 4.855 dB, input return loss <-13 dB and 12.5 mW power consumption. Â Â